Distorsi Nilai Islam dalam Simulakra: Komunikasi Keagamaan di Lingkungan Universitas Islam Negeri Sumatera Utara - Matondang, Abdul Rahman; Kholil, Syukur (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study investigates the symbolic distortion of Islamic values within the framework of simulacrum theory as it applies to religious communication at the Universitas Islam Negeri Sumatera Utara (UINSU). The main research question addresses how Islamic values are simulated and potentially lost in communication practices shaped by institutional bureaucracy, digital platforms, and ceremonial religiosity. Employing a qualitative case study design under a critical paradigm, the research uses in-depth interviews, participant observation, and document analysis. The findings indicate that religious communication at UINSU tends to prioritize representational aesthetics over substantive meaning, often reproducing signs of Islam without spiritual depth. Social media content, official discourses, and campus religious events are dominated by institutional image-building rather than ethical transformation. The study concludes that communication practices have entered a hyperreal condition, necessitating a reorientation toward prophetic and dialogic approaches to restore Islamic values as moral substance rather than institutional display.